QUALITY TRANSFORMATION STRATEGY THROUGH THE INTEGRATION OF LEARNER VISION AND INSTRUCTIONAL LEADERSHIP IN ELEMENTARY SCHOOLS - Zumrotun Zumrotun; Ngurah Ayu Nyoman Murniati; Supandi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The shift in the global education paradigm demands holistic learning quality beyond quantitative achievement. Despite having ICT-literate educators, SD Negeri 1 Godong faces the challenge of numeracy stagnation (70.83%) and character fluctuations. This research is a qualitative case study aimed at analyzing the development of vision, culture, and learning leadership in improving educational quality. Data were collected through interviews, observations, and Education Report Card documents, then analyzed using the interactive model of Miles et al. The results show that the vision of the